Morphological Analysis of Nose in Patients of Tessier No. 0 Cleft With a Bifid Nose in China - Wang, Xin; Wang, Huan; You, Jianjun; Zheng, Ruobing; Xu, Yihao; Zhang, Xulong; Guo, Junsheng; Fan, Fei (Frontiers in Pediatrics, 2021)
Objective Facial Cleft involves complex malformations. No study assessed the facial deformity of Tessier No.0 cleft with a bifid nose. Thus, we used anthropometric measurements to access the nose in patients. Methods A total of 24 bifid nose deformities underwent surgery at our institution between 2010 and 2019. Standardized photographs were taken preoperatively and postoperatively. Landmarks were identified on these images, measurements for nasal analysis were performed and compared with established Chinese norms. Surgical methods differences were also analyzed. Results The median follow-up time was 2.51 years. Postoperatively, there is a significant difference in comparison with preoperative in nasal index, Medial canthus & nose width index, nasolabial angle, nasofacial angle, ala length & nasal bridge length index, nasal tip protrusion & nasal width index and nasal width & ala length index. Further, the medial canthus & nose width index and nasal width & ala length index were significantly larger in ordinary people, while ala length & nasal bridge length index and Nasal tip protrusion & Nasal width Index were smaller. After surgery, most angles and index were standard except nasolabial angle in female and ala length & nasal bridge length index in male. Moreover, as for the group of costal cartilage transplantation, most index and angles have improved after surgery including nasolabial angle, nasofacial angle, ala length & nasal bridge length index, nasal tip protrusion & nasal width Index and nasal width & ala length Index. However, only nasal tip protrusion & nasal width Index, columella length & nasal tip protrusion index and nasal width & ala length index in the silicone prosthesis group implantation has significance. Costal cartilage transplantation can also better improve ala length & nasal bridge length index than the silicone prosthesis implantation. Conclusion Most defects can repair through surgery, but the outcome is a lack of evaluation. Thus, anthropometric assessment can serve as a material for nasal surgery and reconstructive.